Effectiveness of Task-Based Language Teaching Approach on Students’ Academic Performance in Productive Skills of English Language - BUKAR, Mohammed Goni; BULARAFA, Mohammed Waziri; MUSTAPHA, Muhammad Ali; GANA, Iya Aliyu (Ilorin Journal of Education, 2024)
The study examined the effectiveness of Task-based Language Teaching Approach on students’ academic performance in productive skills of English language. The quasi-experimental research design was adopted for the study with three tested hypotheses. The study population comprised three hundred and sixty-five (365) senior secondary school students from Jibwis Multilingual Academy in Maiduguri, Borno State. A convenience sampling technique was employed to select two intact senior secondary (SSII) classes in the school, resulting in a sample size of one hundred and five (105) students. The experimental group consisted of fifty-five students, while the control group consisted of fifty students. The instrument used for the study was a researcher’s self-developed tool named “English Language Productive Skills Performance Test” (ELPSPT). In order to ensure the validity of the instrument, two experts from test and measurement were used. The reliability of the instrument resulted to 0.88 reliability index using Cronbach Alpha reliability method. An Independent samples t-test was used as statistical tool to test all the hypotheses at 0.05 significant level. The findings revealed that the task-based language teaching approach had positively impacted on improving students’ academic performance in speaking and writing skills of the English language. It was recommended that school administrations should encourage teachers to implement teaching methods centered around activities fostering active student engagement and communication in the classroom. Additionally, education bodies at the state level, such as the teaching service board and the state ministry of education, should conduct regular seminars and workshops to enhance teachers’ skills and development.